THE SHAME OF THE WOMAN ON THE ROCK (Heritage, 2022)
Through its focus on the stream of thoughts of Marta L, overwhelmed by worry over the obvious signs of aging, Andrić’s story The Woman on the Rock naturally encourages psychological interpretations. While challenging a psychoanalytic reading, we interpret The Woman on the Rock within the context of Jung’s analytical psychology, employing the concept of archetypes, primarily the shadow, the persona, and the animus. We have pointed to Marta’s grandiose self, the compensatory quality of her memories, as well as her ego ideal and the realization of her persona’s inevitable adaptation. We dedicated a special section to her shame, which hasn’t been given attention in literary science so far. The aging-related shame ongoing in the protagonist’s stream of thought is connected with the shame she felt at the threshold of girlhood in front of others, in an episode that has an evident erotic connotation.Although the story illuminates Marta’s relationships with the important men in her life, the key relationship in this story is Marta’s relationship with herself and her body: the protagonist is preoccupied with self-evaluation, in a tumultuous, but just as necessary process of revalorizing her self-assessment criteria. Marta is a typical father’s daughter, who hasn’t developed her female side because feminine qualities hadn’t been affirmed in her raising. Hence she views her body through the eyes of a strict and judgmental animus, formed in great measure by her father’s figure.
Keywords: Ivo Andrić, The Woman on the Rock, shame, aging, the body, the subconscious, shadow, persona, animus.